Duolingo’s Effectiveness in Enhancing English Reading Skills through Reflective Feedback - Silvi Ayu Mandira; Rini Ekayati (EXCELLENCE: Journal of English and English Education, 2026)
Digital technology has reshaped English language learning by offering learners more personalized, interactive, and accessible practice, with Duolingo emerging as one of the most widely used gamified applications for developing reading skills. This study examined the effectiveness of Duolingo in enhancing English reading skills among seventh-grade students, with particular attention to reflective learning and feedback. A qualitative descriptive design was used, involving 35 students and one English teacher at SMP Muhammadiyah 01 Medan. Data were collected through a Likert-scale questionnaire, semi-structured interviews, observation, and documentation, then analyzed using the interactive model of data reduction, data display, and conclusion drawing proposed by Miles, Huberman, and Saldana. Results suggest that students and the teacher perceived Duolingo positively, especially with its contribution to reading comprehension, vocabulary acquisition and learning motivation, and also in relation to the fostering of more autonomous and introspective study practices. The application’s rapid feedback function allowed students to detect and self-correct their own reading errors, which further fostered a more thoughtful attitude to practice. This study implies Duolingo may serve as a beneficial supplemental tool for reading teaching, so long as teachers continue to push students toward deeper and more critical engagement with text.